Effect of High-Grade Preoperative Knee Laxity on Anterior Cruciate Ligament Reconstruction Outcomes. (December 2016) - Magnussen, Robert A.; Reinke, Emily K.; Huston, Laura J.; ,; Hewett, Timothy E.; Spindler, Kurt P.
Background: Knee laxity in the setting of suspected anterior cruciate ligament (ACL) injury is frequently assessed through physical examination using the Lachman, pivot-shift, and anterior drawer tests. The degree of laxity noted on these examinations may influence treatment decisions and prognosis. Hypothesis: Increased preoperative knee laxity would be associated with increased risk of subsequent revision ACL reconstruction and worse patient-reported outcomes 2 years postoperatively. Study Design: Cohort study; Level of evidence, 2. Methods: From an ongoing prospective cohort study, 2333 patients who underwent primary isolated ACL reconstruction without collateral or posterior cruciate ligament injury were identified. Patients reported by the operating surgeons as having an International Knee Documentation Committee (IKDC) grade D for Lachman, anterior drawer, or pivot-shift examination were classified as having high-grade laxity. Multiple logistic regression modeling was used to evaluate whether having high-grade preoperative laxity was associated with increased odds of undergoing revision ACL reconstruction within 2 years of the index procedure, controlling for patient age, sex, Marx activity level, level of competition, and graft type. Multiple linear regression modeling was used to evaluate whether having high-grade preoperative laxity was associated with worse IKDC score or Knee injury and Osteoarthritis Outcome Score Knee-Related Quality of Life subscale (KOOS-QOL) scores at a minimum 2 years postoperatively, controlling for baseline score, patient age, ethnicity, sex, body mass index, marital status, smoking status, sport participation, competition level, Marx activity rating score, graft type, and articular cartilage and meniscus status. Results: Pre-reconstruction laxity data were available for 2325 patients (99.7%). Two-year revision data were available for 2259 patients (96.8%), and patient-reported outcomes were available for 1979 patients (84.8%). High-grade preoperative laxity was noted in 743 patients (31.9%). The mean postoperative IKDC score was 81.8 ± 15.9, and the mean KOOS-QOL score was 72.0 ± 22.0. The presence of high-grade pre-reconstruction laxity was associated with significantly increased odds of ACL graft revision (odds ratio [OR] = 1.87 [95% CI, 1.19-2.95]; P = .007). The presence of high-grade pre-reconstruction laxity was not associated with any difference in postoperative IKDC (β = −0.56, P = .44) or KOOS-QOL (β = 0.04, P = .97). Conclusion: The presence of high-grade pre-reconstruction knee laxity as assessed by manual physical examination under anesthesia is associated with significantly increased odds of revision ACL surgery but has no association with patient-reported outcome scores at 2 years after ACL reconstruction.